Burden and outcome of neonatal surgical conditions in Nigeria: A countrywide multicenter cohort study - Hyginus Okechukwu Ekwunife; Emmanuel Ameh; Lukman Abdur-Rahman; Adesoji Ademuyiwa; Emem Akpanudo; Felix Alakaloko (EL-Med-Pub, 2022)
Background:  Despite a decreasing global neonatal mortality, the rate in sub-Saharan Africa is still high. The contribution and the burden of surgical illness to this high mortality rate have not been fully ascertained. This study is performed to determine the overall and disease-specific mortality and morbidity rates following neonatal surgeries; and the pre, intra, and post-operative factors affecting these outcomes.  Methods: This was a prospective observational cohort study; a country-wide, multi-center observational study of neonatal surgeries in 17 tertiary hospitals in Nigeria. The participants were 304 neonates that had surgery within 28 days of life. The primary outcome measure was 30-day postoperative mortality and the secondary outcome measure was 30-day postoperative complication rates. Results: There were 200 (65.8%) boys and 104 (34.2%) girls, aged 1-28 days (mean of 12.1 ± 10.1 days) and 99(31.6%) were preterm. Sepsis was the most frequent major postoperative complication occurring in 97(32%) neonates. Others were surgical site infection (88, 29.2%) and malnutrition (76, 25.2%). Mortality occurred in 81 (26.6%) neonates. Case-specific mortalities were: gastroschisis (14, 58.3%), esophageal atresia (13, 56.5%) and intestinal atresia (25, 37.2%). Complications significantly correlated with 30-day mortality (p <0.05). The major risk predictors of mortality were apnea (OR=10.8), severe malnutrition (OR =6.9), sepsis (OR =7. I), deep surgical site infection (OR=3.5), and re-operation (OR=2.9).  Conclusion: Neonatal surgical mortality is high at 26.2%. Significant mortality risk factors include prematurity, apnea, malnutrition, and sepsis.